Lost Nutrition Differences Frozen Milkfish Non Whip Out Spines and Whip Out Spines During Low Storage - Arifiya Ayu Kusuma; Eko Nurcahya Dewi; Ima Wijayanti (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Freezing was one alternative way to maintain the quality of the fish. The purpose of this study was to determine the amount of nutrients lost from frozen fish drip non whip out spines and whip out spines on a long pull at different low storage temperatures of 2-5°C. The method used was experimental laboratory with the basic design of completely randomized design (CRD) with factorial pattern and repeated 3 times. Parameters measured were driploss test, the fat, water, protein and provitamin A contentin the drip,  SEM (Scanning Electron Microscopy) analysis and organoleptic test. Data were analyzed using analysis of variance (ANOVA). The results showed that treatment of non whip out spines and whip out spines fish freezing and storage time gave a significant effect (P<0,05) on driploss; fat, moisture, protein,provitamin A content in the drip;  Morphological image test with SEM (Scanning Electron Microscopy) and organoleptic value. Driploss frozen fish of non whip out spines damaged 2 times greater than  whip out spines, Value provitamin in the drip of non whip out spines frozen fish in the begunning of storage that was  185.28±9.85 µg/100g and in the endof  storage was 257.23±17.00 µg/100g and organoleptic value of non whip out spines was 7.91±0.90 and whip out spines 7.53±1.06 in the end of storage.